Obraz polityka w „Fakcie” - Czajka-Bubniak, Anna (Słowo. Studia językoznawcze, 2017)
The aim of the article is research, how tabloid “Fact” looking at an politician using an image of former premier – Donald Tusk and analyse if this view is typical, characteristic, stereotypical for this kind of paper. The material used in analyses includes texts and pictures. An image of politician is simple because of his destiny to a mediocre reader without education and suffering wrongs in society. The borders between the wealth and poverty are clearly defined in “Fact”.